Analysis Of Heat Treatment Effect On Tensile Properties Of 3D Printed Carbon Fiber Composite And Comparing Mechanical Properties On Manufacturing Method - Chai, Chang Yuan (Universiti Sains Malaysia, 2022)
3D printing is a very popular technology lately because of it is very flexible to fabricate complex design of product with relatively low cost. 3D printing is additive manufacturing which fabricate parts by building with melted filament layer by layer. Carbon fiber reinforced polymer is a strong material with light weight. Carbon fiber composite can be quite costly to fabricate and it is commonly used in automotive, aerospace and medical field. 3D printed carbon fiber reinforced polymer (CFRP) is still a very new topic in recent years. In this project, 3D printed carbon fiber reinforced polylactic acid (CF-PLA) is fabricated by Fused Deposition Modelling (FDM) process. Effect of heat treatment on tensile strength 3D printed CF-PLA is investigated. 3D printed CF-PLA with 95℃ annealing temperature and 90 minutes annealing duration showed highest increase with 5.8% of tensile strength. The result of flexural test showed aircraft component carbon fiber composite has much more mechanical strength compared to 3D printed CF-PLA. However, 3D printed CF-PLA has better ductility which has approximately two times of maximum flexure extension compared to aircraft component carbon fiber composite. Carbon fiber reinforced with other polymer such as Acrylonitrile Butadiene Styrene (ABS) and Polyethylene Terephthalate Glycol (PETG) are suggested for future research to discover more potential in 3D printed carbon fiber composite.